THE IMPACT OF BEAUTY STANDARDS ON THE CHOICE OF SURGICAL PROCEDURES AND THE INCIDENCE OF DYSMORPHIC DISORDER AMONG STUDENTS AT THE EVANGELICAL UNIVERSITY OF GOIÁS. (CIPEEX, 2025)
Objective: To evaluate the growing wave of dissatisfaction with one's own image, leading to the adoption of excessive cosmetic procedures among young people. Method: This research is a descriptive cross-sectional study, in which the self-perception of young academics at UniEVANGÉLICA was evaluated with scientific rigor, based on BMI assessment and responses to the Beyond the Mirror and Body Shape Questionnaire (BSQ) questionnaires.Results: Conclusion: it is believed that UniEVANGÉLICA students are concerned about their appearance and adopt measures such as diets, physical activities, and cosmetic procedures to feel better about their physical appearance, but without causing physical and psychological harm.
Keywords: Beauty standards; aesthetics; body dysmorphic disorder; self-perception; body